Transcriptomic changes underlying glucocorticoid-induced suppression of milk production by dairy cows - Sadovnikova, Anna; Garcia, Sergio C.; Trott, Josephine F.; Mathews, Alice T.; Britton, Monica T.; Durbin-Johnson, Blythe P.; Hovey, Russell C. (Frontiers in Genetics, 2022)
Milk production by dairy cows is sensitive to increased levels of stress hormones such as glucocorticoids (GC) that also regulate the transcription of several genes required for milk synthesis. Whereas previous studies identified that an exogenous GC such as dexamethasone (DEX) transiently suppresses milk yield in several species without any pronounced effect on milk protein or fat percentage, the mechanism underlying this effect has not been established. In this study we sought to establish changes within the mammary glands of non-pregnant dairy cows in their second lactation (n=3-4; 648-838 kg) following a single dose of exogenous DEX. Changes in the udder were monitored by serial biopsy of alternating quarters, concurrent with quarter-level monitoring of milk yield and composition. Dexamethasone increased serum glucose levels from 12-36 h (P<.05), reduced milk yield from 12-48 h (P<.05), increased % milk protein content at 24 h post-DEX, and transiently decreased both milk lactose and -lactalbumin content, while not altering the level of milk fat. After 72 h, all aspects of milk production had returned to pre-treatment levels. Transcriptomic changes in the mammary glands in response to DEX were identified by RNA sequencing followed by differential gene expression analysis. Coincident with the milk yield and composition changes was the differential expression of 519 and 320 genes at 12 and 24 h after DEX (adjusted P<.05), respectively, with the return of all gene expression to baseline levels by 72 h. Among the transcriptomic changes in response to DEX, there was notable downregulation of elements in the lactose synthesis pathway, specifically AQP3, GALE and LALBA (-lactalbumin) at 12 h, and sustained downregulation of LALBA at 24 h. One gene in the pathway, UGP2, was upregulated at 12-24 h post-DEX. This work supports the hypothesis that there is a direct relationship between the response to DEX and the concurrent suppression of milk yield due to the reduced synthesis of -lactalbumin and lactose by the mammary epithelium. The ability of glucocorticoids to modulate the homeorrhetic requirements for glucose during stressful states concurrent with immune activation bears significance for dairy animals as well as a broad range of lactating mammals.